Epidemiological trends of dengue disease in Mexico (2000-2011): a systematic literature search and analysis. - Héctor Gómez Dantés; José Arturo Farfán-Ale; Elsa Sarti (Public Library of Science (PLoS), 2014)
This systematic literature review describes the epidemiology of dengue disease in Mexico (2000-2011). The annual number of uncomplicated dengue cases reported increased from 1,714 in 2000 to 15,424 in 2011 (incidence rates of 1.72 and 14.12 per 100,000 population, respectively). Peaks were observed in 2002, 2007, and 2009. Coastal states were most affected by dengue disease. The age distribution pattern showed an increasing number of cases during childhood, a peak at 10-20 years, and a gradual decline during adulthood. All four dengue virus serotypes were detected. Although national surveillance is in place, there are knowledge gaps relating to asymptomatic cases, primary/secondary infections, and seroprevalence rates of infection in all age strata. Under-reporting of the clinical spectrum of the disease is also problematic. Dengue disease remains a serious public health problem in Mexico.